Vibration fatigue comparative test and life prediction for titanium alloy connection structures - HE Shi; LIU Xiaochuan; LIU Haihan; LI Kaixiang; BAI Chunyu (Hangkong gongcheng jinzhan)
A large number of mechanical connection structures in aircraft face vibration fatigue problems，and the evaluation of vibration fatigue performance is the key to determine the service life，safety design and evaluation of the structure. In order to study the vibration fatigue performance of typical titanium alloy connection structures，the typical connection structures with different support shapes and rivet spacing are designed based on TC4 titanium alloy thin plates，a vibration fatigue test system is built，and the vibration fatigue performance of different connection structures under narrowband random loads is compared through experiments. The method for predicting the vibration fatigue life of connection structures based on random vibration Srms-N curves is proposed by introducing stress severity coefficients and fatigue notch factor. The results show that under similar vibration stress levels，the vibration fatigue performance of the T-shaped support connection structure is better than that of U-shaped support structure；on the premise of ensuring the strength of the connection，increasing the spacing between rivets appropriately can improve the vibration fatigue resistance of the connection structure；after introducing the stress severity factor and fatigue notch factor，the vibration fatigue life of the connection structure is significantly improved，and the difference between the predicted life and the test results is within 30%.